Study on Intestinal Parasitic Infections in Muslim community of Janakpurdham, Nepal (Janaki Medical College Journal of Medical Science, 2017)
Background and Objectives: Intestinal parasitic infection is an important public health problem in Nepal because of its high morbidity and mortality. The distribution and prevalence of the various intestinal parasites species depend on social, geographical, economical and inhabitant customs. Therefore, the present study was designed to determine the burden of intestinal parasitic infections and its relation with sanitary practices and socio-demographic characteristics in Muslim community of Janakpurdham, Nepal.Material and Methods: A total of 161 stool samples were collected in dry, clean and screw capped plastic container and were preserved with 10% formalin. The stool samples were examined by direct microscopy and confirmed by concentration methods. Modified Ziehl Neelsen (ZN) staining was performed for the detection of coccidian parasites. P- value < 0.05 was considered as statistically significant.Results: The incidence of intestinal parasitic infection was 63.35% (male = 57.84% vs. female = 42.15%) (p = 0.321). The positive cases of parasitic infection were found to be slightly higher in less than 10 years (35.29%) than others. Hookworm (10%) and G. lamblia (28%) infection was marginally higher than other helminthic and protozoan infection. The highest number of positive cases of parasitic infection was found in those who didn’t wash their hands before meal, defecates stool haphazardly in open area, didn’t wash their hands after toilet, didn’t trim their nail, in larger family, with low income and in housewives which was found to be statistically significant (p =